A magnetron-like interaction structure for Gyro-TWTs - Singh G.; Basu B.N.; Kartikeyan M.V.; Thumm M. (My University, 2025)
The gyro-TWT has the potential to generate high powers over a wide frequency band in the microwave and millimeter part of the spectrum. These gyro-amplifiers are being developed for applications requiring phase coherence and instantaneous bandwidth, such as in linear accelerators and millimeter wave radars. In this work, the dispersion characteristics and gain-frequency response for different modes of a magnetron like interaction structure for a gyro-TWT are presented. ©2004 IEEE.